2014
DOI: 10.1017/s0022215114001017
|View full text |Cite
|
Sign up to set email alerts
|

Endolymphatic sac surgical anatomy and transmastoid decompression of the sac for the management of Ménière's disease

Abstract: The endolymphatic sac may be identified on inspection by an overlying patch of dura, thereby reducing exploratory dissection. It is best to decompress the sac as far proximally as possible, whilst protecting the posterior semicircular canal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 13 publications
0
15
0
1
Order By: Relevance
“…Although endolymphatic sac surgery has been established since 1927, this ambiguity about the effectiveness of surgical intervention in the form of ESD still exists ( 21 23 ). Locke ( 24 ) reported that the unpredictability of the outcomes of surgical decompression might be related to the difficulty in locating and fully decompressing the endolymphatic sac. Moreover, prolonged exploration of the cystic region may increase the risk of complications due to damage to the cystic cavity and its surrounding structures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although endolymphatic sac surgery has been established since 1927, this ambiguity about the effectiveness of surgical intervention in the form of ESD still exists ( 21 23 ). Locke ( 24 ) reported that the unpredictability of the outcomes of surgical decompression might be related to the difficulty in locating and fully decompressing the endolymphatic sac. Moreover, prolonged exploration of the cystic region may increase the risk of complications due to damage to the cystic cavity and its surrounding structures.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, prolonged exploration of the cystic region may increase the risk of complications due to damage to the cystic cavity and its surrounding structures. Locke recommended that bone should be removed from the superior petrosal sinus to the jugular bulb and from a point medial to the posterior semicircular canal and posterior to the sigmoid sinus ( 24 ). The endolymphatic sac was located by measuring the lower limit of the posterior semicircular canal and maintained outside the posterior semicircular canal for decompression in LESD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a 2014 anatomical study of the temporal bone, Locke et al32 explained that one possible reason for the inconsistent results obtained with endolymphatic sac surgeries is that the sac itself is difficult to identify and a proper decompression is not often accomplished, much less a proper drainage. The reason for this is that the intradural component of the sac varies in size and position.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Endolymphatic sac surgery is a contentious issue in Ménière's disease treatment. In the current issue, Locke and colleagues describe the surgical anatomy of the endolymphatic sac and suggest that the results of surgical decompression may be unpredictable because the sac is difficult to locate and decompress adequately 2 . In another ‘pressure-related’ otological article, Mitchell-Innes and colleagues discuss air travellers' awareness of the preventability of otic barotrauma 3 .…”
mentioning
confidence: 99%